Fault tolerance of a quadrotor via feedback linearization approach - Jebelli, Ali; Najafiyanfar, Alireza; Mahabadi, Arezoo; E. Yagoub, Mustapha C. (Institute of Advanced Engineering and Science, 2023)
A control algorithm is proposed to efficiently control the state, position, and height of a nonlinear dynamic model of a quadcopter. Based on feedback linearization, a state space model is presented for the system with the controller with a two-loop control structure designed and implemented in it. The inner and faster controller is responsible for adjusting the quadcopter height and angles, and the outer and slower controller is responsible for changing the desired figures of roll and pitch angles to control the system position. Whenever a rotor of the quadcopter rotor fails, the status and position of the system are converged and the system is stabilized. Simulation results based on different scenarios indicate the proper performance of the control system whenever there are external disturbances. Note that the gyroscopic effects because of the propeller rotation were not considered.